HUBUNGAN ANTARA SLEEP HYGIENE DENGAN TINGKAT INSOMNIA PADA LANSIA DI KECAMATAN JEBRES KELURAHAN GANDEKAN RW 05 SURAKARTA - Putri Wulan Dhari; Ika Silvitasari (Nusantara Hasana Berdikari, 2022)
Insomnia is the most common sleep disorder experienced by the elderly. Sleep disturbances in the elderly can have a negative impact, especially on the health conditions of the elderly. Sleep hygiene is a way of training to form habits so that sleep becomes quality based on activities carried out before bed. The purpose of the study was to determine